Comprehensive evaluation and scenario simulation for the water resources carrying capacity in Xi'an city, China. (15th January 2019) - Yang, Zhaoyang; Song, Jinxi; Cheng, Dandong; Xia, Jun; Li, Qi; Ahamad, Muhammad Irfan
Abstract: The quantity and quality of water resources are of great importance in maintaining urban socio-economic development. Accordingly, substantial research has been conducted on the concept of the water resources carrying capacity (WRCC). In this study, analytic hierarchy process (AHP) and system dynamics (SD) models were combined to construct a multi-criteria evaluation system of the WRCC and a socio-economic/water resources SD model for Xi'an. The developmental trends of the society, economy, water supply/demand, and wastewater discharge were obtained from 2015 to 2020 using five scenarios designed for distinct purposes; these scenarios and trends were comprehensively evaluated using a combination of qualitative and quantitative analyses. The results indicated that the WRCC (0.32 in 2020) in Xi'an will shift from a normal to a poor state if the current social development pattern is maintained; therefore, we conclude that the socio-economic development of Xi'an is unsustainable. However, under a comprehensive scheme, the WRCC index (0.64 in 2020) will increase by 48% compared with the WRCC index under a business-as-usual scenario. Further, some practical suggestions, including the promotion of industrial reforms and the improvement of water-use efficiency and recycling policies, were provided for improving the regional WRCC. Highlights: A regional water resources carrying capacity (WRCC) assessment system was established which applying to the study area. Socio-economic/water resources processes coupled and simulated using system dynamics approach. The key to improving the WRCC is the conservation of agricultural water consumption.